Pengembangan Model Latihan Teknik Dasar Tendangan Taekwondo Berbasis Permainan Untuk Anak Usia 7 – 12 tahun di Kabupaten Pringsewu Provinsi Lampung - ZikoFajarRamadhan Ziko; Satria Armanjaya Satria; Riris Novrian Prayoga Riris (Performa, 2026)
This study aims to determine the effectiveness of the development of a game-based Taekwondo kicking basic technique training model for children aged 7-12 years in Pringsewu Regency, Lampung Province. The method used in this study is a mixed method while the research design used is a pre-test-post-test group design. The population in this study were athletes from the Dojang Nawasena Club Lampung with a sample of 34 athletes from the total sample used, so this study is called a population study. The data collection technique for kicking results uses the Basic Kicking Technique instrument. The results of the study show that there is a significant influence from the development of a game-based Taekwondo kicking basic technique training model for children aged 7-12 years in Pringsewu Regency, Lampung Province, getting a t-value of 19.58> 1.782